Principles of Biochemistry - Voet, Donald Voet ,Judith G (John Wiley, 2012)
Voet and Pratt's 4th edition of Fundamentals of Biochemistry, challenges readers to better understand the chemistry behind the biological structure and reactions occurring in living systems.